Rapid Detection of mecA and femA Genes by Loop-Mediated Isothermal Amplification in a Microfluidic System for Discrimination of Different Staphylococcal Species and Prediction of Methicillin Resistance - Meng, Xiangrui; Zhang, Guohao; Sun, Bo; Liu, Shujun; Wang, Yadong; Gao, Ming; Fan, Yubo; Zhang, Guojun; Shi, Guangzhi; Kang, Xixiong (Frontiers in Microbiology, 2020)
Staphylococcal infection is one of the most pressing problems in modern medicine due to the increasing antibiotic resistance with the overuse of antibiotics. Conventional methods for identification and antimicrobial susceptibility testing (AST) generally take 3-7 days and require skilled technicians. In this study, a microfluidic device based on loop-mediated isothermal amplification (LAMP) was developed, which could discriminate S. aureus, S. epidermidis, S. haemolyticus and S. hominis and determine their methicillin susceptibility by targeting the mecA and femA genes within 70 min including the hands-on time. Multiplex and real-time detection was achieved in a closed system without aerosol contamination. The limits of detection (LODs) for S. aureus, S. epidermidis, S. hominis and methicillin-resistant S. aureus (MRSA) were 20 CFU/reaction while that for S. haemolyticus was 200 CFU/reaction. A total of 102 positive cultures of cerebrospinal fluid (CSF) were also tested and the results were in good agreement with those from conventional methods. Furthermore, mixed cultures were readily identified by our method. The portable and integrated device is rapid, accurate and easy to use, which can provide information for prompt institution of proper antimicrobial therapy and has great potential for clinical applications, especially in resource-limited settings.